PENGARUH LATIHAN INTERVAL PLY OMET RIK BURPEE TERHADAP PENINGKATAN DAYA TAHAN FISIK ATLET SSB KANUGAS TAHUN 2025 - Revael Mey Hagata Sembiring; Deasyi Natalia Sitepu; Julius Boy Nesra Basgimata Barus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of interval plyometric burpee training on improving the physical endurance of SSB Kanugas athletes in 2025. The research used an experimental method with a One Group Pretest-Posttest Design. The sample consisted of 10 athletes selected using purposive sampling technique. The research instrument used was the Bleep Test to measure athletes’ physical endurance. The training program was conducted for 4 weeks with a frequency of 2 sessions per week. Data were analyzed using the Paired Sample t-Test at a significance level of 5%.The results showed an improvement in athletes’ physical endurance after the treatment, with the average pre-test score of 5.73 increasing to 7.21 in the post-test. Statistical test results indicated that interval plyometric burpee training had a significant effect on improving the physical endurance of SSB Kanugas athletes.